2023
DOI: 10.3389/fpsyt.2023.1196569
|View full text |Cite
|
Sign up to set email alerts
|

The role of only-child status in the effect of childhood trauma and parental rearing style on depressive symptoms in Shanghai adolescents

Abstract: IntroductionAfter decades of the one-child policy, China changed its rules to allow two children in 2016, which altered family dynamics. Few studies have examined the emotional problems and the family environment of multi-child adolescents. This study aims to explore the role of only-child status in the impact of childhood trauma and parental rearing style on depressive symptoms of adolescents in Shanghai, China.MethodsA cross-sectional study was conducted on 4,576 adolescents (M = 13.42 years, SD = 1.21) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…To our knowledge, there is a general consensus among current researchers that boys are at a higher risk of developing dyslexia than girls ( Arnett et al, 2017 ; Feng et al, 2022 ; Yang et al, 2022 ). In line with a prior study, the gender of children had an impact on parenting styles ( Zhong et al, 2023 ). Boys are given more responsibility, and parents are harsher, more rejecting and neglectful of boys, especially fathers, who are more likely to be strict with boys in home education.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To our knowledge, there is a general consensus among current researchers that boys are at a higher risk of developing dyslexia than girls ( Arnett et al, 2017 ; Feng et al, 2022 ; Yang et al, 2022 ). In line with a prior study, the gender of children had an impact on parenting styles ( Zhong et al, 2023 ). Boys are given more responsibility, and parents are harsher, more rejecting and neglectful of boys, especially fathers, who are more likely to be strict with boys in home education.…”
Section: Discussionsupporting
confidence: 85%
“…Parenting styles are the methods and forms commonly used by parents in the raising and education of their children, with a relatively stable style of behavior ( Guo et al, 2022 ). Parenting styles permeate the parent–child interaction process and have a significant impact on children’s personality, mental health, and especially their academic performance ( Watson et al, 2023 ; Zhong et al, 2023 ). Parenting styles are categorized into four types: emotional warmth, rejection, overprotecting and anxious rearing.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is a general consensus among current researchers that boys are at a higher risk of developing dyslexia than girls [4,33,42]. In line with a prior study, the gender of children had an impact on parenting styles [15]. Boys are given more responsibility, and parents are harsher, more rejecting and neglectful of boys, especially fathers, who are more likely to be strict with boys in home education.…”
Section: Discussionmentioning
confidence: 65%
“…Parenting styles are the methods and forms commonly used by parents in the raising and education of their children, with a relatively stable style of behavior [14]. Parenting styles permeate the parent-child interaction process and have a signi cant impact on children's personality, mental health, and especially their academic performance [15,16]. More speci cally, negative parenting styles seem to increase risk of emotional and behavioral problems among children [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further, children and adolescents from multichild families might perceive greater childhood trauma and parental rejection [53 ▪▪ ] and could be concerned about whether their parents treat them equally as other children [54]. In families with multiple children, negative rearing styles of parents could lead to maladaptive behavioural patterns in early adolescence, while insecure attachment styles and low self-worth could result in negative emotions such as depression and interpersonal sensitivity [53 ▪▪ ]. Previous evidence also indicated that their mental health status could worsen as the number of siblings increased [1].…”
Section: Discussionmentioning
confidence: 99%